UJI AKTIVITAS ANTIOKSIDAN DAN SIFAT ORGANOLEPTIK TEH HERBAL CAMPURAN DAGING BUAH PARE (MOMORDICA CHARANTIA L.) DAN KULIT BUAH NAGA MERAH (Hylocereus Lemairei (HOOK.) BRITTON & ROSE) - Yulisma Sudarsi; Musyirna Rahmah Nst (LPPM Universitas Muhammadiyah Riau, 2018)
Herbal tea is a herbal mixture made from flowers, leaves, seeds and or roots of various plants. Some of herbal tea consumed for adds energizing, help relaxation, overcome digestive problems and also strengthen the immune system. Research on antioxidant activity and organoleptic characteristic mixflesh of bitter melon fruit (Momordica charantia L.) and red dragon fruit skin (Hylocereus lemairei (Hook.) britton & rose) herbal tea has been done. The objective of this research was to make a herbal tea formulation that has a high antioxidant activity and is preferred from a mixture of bitter melon fruitand red dragon fruit skin that has been dried at 50-60°C. The antioxidant activity were measured by free radical scavenging method with DPPH; whereas organoleptic test was measured by hedonik method. The results of 5 formulas indicate that antioxidant activity is the highest in FIII formula that has the most content of bitter melon fruit. Data were analyzed using one way ANOVA and Tukey method at 99% confidence level. The herbal tea formulation of a coarse powder mixture of 1.75 g of bitter melon fruit and a coarse powder of 0.25 g red dragon fruit showed the highest antioxidant activity with percent inhibition of 98,249% and preferably with the likes after adding 30 mL of honey.